New pharmacological targets against COVID-19: the use of interferons for activating the antiviral state and eliminating the SARC-CoV-2 virus (Research, Society and Development, 2021)
SARS-CoV-2 virus, cause of COVID-19 disease, was described at first in Wuhan (China) December 2019, infecting more than 170 million people. During viral infection, innate immune system initially acts with cell signaling leading to the production and release of pro-inflammatory cytokines, mostly characterized by low levels of interferons (IFNs), which stimulate the expression of genes that contribute to the displacement of host cells towards an antiviral state. In the SARS-CoV-2, the expression and functions of IFN-I are relatively suppressed. This study aims to evaluate the therapeutic potential of using Interferon in activating the antiviral state, especially in the early stages of the disease. This is an integrative literature review, using an exploratory and descriptive methodology. The data were organized in order to list the studies related to the theme in question, the filtering of the articles found had as inclusion criteria, articles in the years 2020 and 2021 (except for one of them, in the year of 2015), in the languages: Portuguese, English and Spanish. Considering that SARS-CoV-2 suppresses the expression of IFN-I and the genes induced by IFN, interrupting the immune defense mechanisms, there is a relationship of IFN suppression with the worsening of the clinical picture in patients with COVID-19. So that, literature elucidates that the exogenous administration of IFN-I has been shown to reduce the severity of symptoms, however, this mechanism needs to be analyzed more clearly.